Assessment of Nail Growth by Election Ink Mark in Normal and Co-morbid Individuals: A Prospective Observational Study - Siddharth Shah; Shubham Darda; Jitendra Lakhani; Vis halkumar Rameshbhai Kathrotiya; Shiv amkumar Patel; Maulikumar Karpatiya; Satyam Kumar; Som Jitendra Lakhani (Journal of Clinical and Diagnostic Research)
Introduction: During an election, an individual who casts a ballot is identified by the indelible electoral ink on their left index fingernail. Since nails are thought of as a window to internal organs, the disappearance of this ink mark from the nail and skin can be seen as a surrogate sign of the growth of nail and skin tissue in both healthy and diseased individuals. Aim: To investigate nail growth by observing indelible election nail ink marks in normal nails and in patients with systemic illnesses that affect the nails. Materials and Methods: This prospective observational study was conducted during India’s 18th Lok Sabha General Election, which took place from 19 April 2024 to 1 June 2024. Approval was obtained prior to the study. Participants were split into two groups: those with healthy nails and those with systemic disorders that impact the nails. Consent was obtained from the participants, who were asked to take serial digital photographs of the left index fingernail on four occasions (on voting day, once after the ink mark had left the skin and remained on the nail, once after approximately one month ±2 days and once at the end when the election ink mark had vanished). Results: Out of 312 participants (168 males and 144 females), 198 were healthy and 114 had co-morbidities. The mean time for the disappearance of the ink mark for participants with co-morbidities affecting the nails was 57.8±14.6 days, which was less than the mean time for disappearance for healthy participants (60.9±13.1 days). The findings, however, lacked statistical significance (p-value=0.06124). The disappearance of skin marks in both normal and co-morbid individuals was approximately a week. It was observed that patients with clubbing exhibited a faster rate of disappearance than those with other co-morbidities, with an average of 52.8±12.2 days. Conclusion: The development of nails slows down with age, although it can accelerate under systemic conditions. The findings, however, lacked statistical significance.